EFFICACY OF SAND FILTRATION, Moringa oleifera SEED AND ALUM TREATMENT IN REDUCTION OF COLIFORMS AND TOTAL BACTERIA IN STABILIZATION POND EFFLUENT - Babatunde A, Awopetu; Ikechuwkw, Moses; Odeyemi, Olu (Department of Microbiology, Obafemi Awolowo University, Ile- Ife, Osun State, Nigeria, 2023)
International Journal of Tropical Medicine and Public Health, Vol. 1,No. 1,p. 40-44